Conceptualizing the implementation of the Merdeka Mengajar platform - Handayani, Sylvia Gusti; Elida, Elida; Rahmiati, Rahmiati; Giatman, Muhammad (Indonesian Research Journal in Education |IRJE|, 2026)
This study aims to conceptualize the implementation of the Merdeka Mengajar Platform (PMM) in vocational education at SMK Negeri 3 Kota Solok from both theoretical and practical perspectives. The research employs a qualitative approach, using a literature review supported by field data collected through observation and documentation. The findings indicate that PMM contributes to improving learning flexibility, access to learning resources, and teachers’ pedagogical competence. However, its implementation still faces several challenges, including limited technological infrastructure, disparities in teachers’ digital competencies, and low levels of optimal use of platform features. These findings highlight that successful PMM implementation is influenced by technological readiness, policy support, and continuous professional development. This study provides a conceptual contribution to the integration of technology into vocational education and practical recommendations for optimizing the implementation of PMM.